Determinación del impacto en la latencia al implementar una librería híbrida de cifrado de tramas entre soluciones .NET y React - Burneo Valencia, David Alejandro (2025)
This project focuses on developing, implementing, and evaluating a hybrid encryption library utilizing the AES and RSA algorithms, aimed at securing REST communications between a React frontend and a .NET backend. Previous studies emphasize the effectiveness of symmetric encryption (AES) for managing large data volumes and the strength of asymmetric encryption (RSA) for secure key exchange. By combining these two methods, hybrid encryption successfully addresses the limitations of each approach when used alone. The library was designed based on Clean Architecture principles, ensuring maintainability and scalability. It was integrated and tested within a distributed application, deployed on both the client and the server. To measure the latency introduced by the encryption and decryption processes, profiling tools such as the JavaScript “performance.now()” API was used. Evaluations included tests with encrypted and plaintext data in multiple HTTP methods (GET, POST, DELETE), under different workloads. The results indicate that while the library does introduce some additional latency, the impact remains within acceptable limits. In the conducted tests, response times were consistently under 100 milliseconds. This demonstrates that the hybrid approach effectively balances security and efficiency, overcoming the challenges posed by using exclusively symmetric or asymmetric encryption models. Therefore, its applicability in real-world environments is validated. Keywords: Hybrid Encryption, AES, RSA, Latency